Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

x - y = -1 ; 3x - 2y = 6

Sagot :

Solve for the first variable in one of the equations, then substitute the result into the other equation.

View image miachirinos

Answer:

x = 8

y = 9

Step-by-step explanation:

x - y = -1

Add y to both sides to get x by itself:

x = -1 + y

3(-1 + y) - 2y = 6

-3 + 3y - 2y = 6

-3 + y = 6

y = 9

x - 9 = -1

x = 8

Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.